2022
DOI: 10.3390/app12136772
|View full text |Cite
|
Sign up to set email alerts
|

Test Suite Prioritization Based on Optimization Approach Using Reinforcement Learning

Abstract: Regression testing ensures that modified software code changes have not adversely affected existing code modules. The test suite size increases with modification to the software based on the end-user requirements. Regression testing executes the complete test suite after updates in the software. Re-execution of new test cases along with existing test cases is costly. The scientific community has proposed test suite prioritization techniques for selecting and minimizing the test suite to minimize the cost of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…to make full use of existing software development resources and experiences and to improve the reusability of software, while reducing development costs and improving development efficiency. A study conducted in 1997 showed that code search has become the most common activity in software development activities [1]. The study showed that developers would construct an average of 12 query statements per workday to search for problems encountered.…”
Section: Introductionmentioning
confidence: 99%
“…to make full use of existing software development resources and experiences and to improve the reusability of software, while reducing development costs and improving development efficiency. A study conducted in 1997 showed that code search has become the most common activity in software development activities [1]. The study showed that developers would construct an average of 12 query statements per workday to search for problems encountered.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcement learning techniques have been successfully applied to various fields [7][8][9][10]. In software testing, Waqar et al [11] proposed a reinforcement learning-based methodology for test suite prioritization. Their results show promise in detecting faults in regression testing.…”
Section: Related Workmentioning
confidence: 99%
“…A conceptual data model was suggested [24] for retrieving data sources and their connections in a standard CI environment. This model defined a set of characteristics used in related investigations, applied The TCP model using an optimization technique and an RL model was initiated [26] to handle large scale test suites. This model complied log files of developers and users using activity tracking technologies by using the RL model to determine future rewards and used an error seeding approach to check software specialist performance.…”
Section: Literature Surveymentioning
confidence: 99%